Apatinib combined with chemotherapy or concurrent chemo-brachytherapy in patients with recurrent or advanced cervical cancer: A phase 2, randomized controlled, prospective study. Issue 11 (March 2020) - Guo, Qiufen; Sun, Yawen; Kong, Enqi; Rao, Linli; Chen, Jinlong; Wu, Qian; Zhang, Tingting; Liu, Naifu; Li, Mingjiang; Sun, Li
Abstract: Objective: Apatinib mesylate is a novel vascular endothelial growth factor receptor 2 (VEGFR-2) inhibitor, which has exhibited good safety and efficacy in several types of solid tumors. The present study aimed to assess the clinical efficacy and safety of apatinib combined with chemotherapy and concurrent chemo-brachytherapy (CCBT) in patients with recurrent and advanced cervical cancer. Methods: A total of 52 patients with first diagnosed recurrent or untreated International Federation of Gynecology and Obstetrics stage IVB cervical cancer admitted at Shandong Cancer Hospital and Institute between July 2016 and May 2018 were analyzed in the current randomized controlled trial. The patients were randomly divided into 2 groups: the apatinib-treated group and the control group. Patients with recurrent cervical cancer in the apatinib-treated group were administered apatinib and carboplatin-paclitaxel as first-line chemotherapy. Patients with advanced cervical cancer were administered apatinib in combination with CCBT. In control group, patients with recurrent cervical cancer were treated with chemotherapy alone while patients with advanced cervical cancer received CCBT. Results: The progression-free survival was significantly prolonged in apatinib group compared with control group (10.1 months; 95% confidence interval (CI), 8.42–11.79 vs 6.4 months; 95% CI, 3.88–8.92; P  < .01; hazard ratio (HR), 0.44; 95% CI, 0.25–0.78; P  < .01). The objective response rate in apatinib group was obviously higher than that in control group (64.3% vs 33.3%, P  < .05). Proteinuria, hand–foot syndrome, mucositis, and hypertension in all Grades were statistically more common in apatinib group than in control group. Apatinib did not obviously aggravate other radiotherapy or chemotherapy side effects. Conclusion: Apatinib exhibited promising clinical efficacy in cervical cancer patients, resulting in an improved response rate and prolonged progression-free survival compared with the control group, and had manageable side effects. Our study revealed that apatinib combination therapy, adenocarcinoma, and bone metastasis